Fine root dynamics in lodgepole pine and white spruce stands along productivity gradients in reclaimed oil sands sites. Issue 20 (2nd October 2015) - Jamro, Ghulam Murtaza; Chang, Scott X.; Naeth, M. Anne; Duan, Min; House, Jason
Abstract Open‐pit mining activities in the oil sands region of Alberta, Canada, create disturbed lands that, by law, must be reclaimed to a land capability equivalent to that existed before the disturbance. Re‐establishment of forest cover will be affected by the production and turnover rate of fine roots. However, the relationship between fine root dynamics and tree growth has not been studied in reclaimed oil sands sites. Fine root properties (root length density, mean surface area, total root biomass, and rates of root production, turnover, and decomposition) were assessed from May to October 2011 and 2012 using sequential coring and ingrowth core methods in lodgepole pine (Pinus contorta Dougl.) and white spruce (Picea glauca (Moench.) Voss) stands. The pine and spruce stands were planted on peat mineral soil mix placed over tailings sand and overburden substrates, respectively, in reclaimed oil sands sites in Alberta. We selected stands that form a productivity gradient (low, medium, and high productivities) of each tree species based on differences in tree height and diameter at breast height (DBH) increments. In lodgepole pine stands, fine root length density and fine root production, and turnover rates were in the order of high > medium > low productivity sites and were positively correlated with tree height and DBH and negatively correlated with soil salinity (P < 0.05). In white spruce stands, fine root surface area was the only parameter that increased along the productivity gradient and was negatively correlated with soil compaction. In conclusion, fine root dynamics along the stand productivity gradients were closely linked to stand productivity and were affected by limiting soil properties related to the specific substrate used for reconstructing the reclaimed soil. Understanding the impact of soil properties on fine root dynamics and overall stand productivity will help improve land reclamation outcomes.